1997
DOI: 10.1074/jbc.272.10.6671
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Moiety of CDC25Mm, a GDP/GTP Exchange Factor of Ras Proteins, Controls the Activity of the Catalytic Domain

Abstract: This work describes the in vitro properties of fulllength CDC25 Mm (1262 amino acid residues), a GDP/GTP exchange factor (GEF) of H-ras p21. CDC25 Mm , isolated as a recombinant protein in Escherichia coli and purified by various chromatographic methods, could stimulate the H-ras p21⅐GDP dissociation rate; however, its specific activity was 25 times lower than that of the isolated catalytic domain comprising the last C-terminal 285 residues (C-CDC25 Mm285 ) and 5 times lower than the activity of the C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 32 publications
2
45
1
4
Order By: Relevance
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Results in vitro with CDC25Mm (13) and in vivo with SOS (14) indicated that the N-terminal portion of GEF down-regulates the activity of the catalytic domain. Several reports have shown that activation of CDC25Mm is coupled with Ca 2ϩ influx, as well as with formation of a complex with calmodulin and phosphorylation (8,15).…”
mentioning
confidence: 99%
“…The cell culture, chilled to 4°C, was centrifugated at 5,000 ϫ g for 10 min and the pellet resuspended in 10 ml of 25 mM Tris-HCl, pH 7.5, 50 mM NaCl, 10% glycerol, 7 mM ME, and 0.5 mM Pefabloc-SC. After sonication (five times for 15 s each), the suspension was centrifuged at 25,000 ϫ g for 20 min at 4°C and the supernatant was mixed batchwise with 5 ml of glutathione-Sepharose 4B (Amersham Pharmacia Biotech) or 5 ml of amylose resin (New England Biolabs), and gently shaken for 30 min at 4°C, as reported previously (13,22). The resin was washed four times with 25 mM Tris-HCl, pH 7.5, 50 mM NaCl, 7 mM ME and the protein eluted with glutathione (3 mg/ml) or maltose (10 mM) solutions in the same buffer.…”
mentioning
confidence: 99%
“…The interaction of GRP with Ca 2+ -CaM leads to GRF activation in intact cells, however, this effect does not occur in vitro. 10,11 It has therefore been proposed that the effect of Ca 2+ -CaM in vivo may be indirect, modulating the interaction of RasGRF with its targets. 10 Calcium signals could also contribute to GRF activation by promoting the proteolytic removal of the N-terminal domain, as it has been shown in vitro.…”
Section: Regulation Of Gdp/gtp Exchangementioning
confidence: 99%
“…10 Calcium signals could also contribute to GRF activation by promoting the proteolytic removal of the N-terminal domain, as it has been shown in vitro. 11 A novel member of the family of Ras-GEFs has recently been cloned from brain 12 and lymphoid tissues. 4 This factor, named RasGRP, possesses calcium and diacyglycerol-binding domains and may directly couple changes in diacylglycerol and possibly calcium concentrations to Ras activation.…”
Section: Regulation Of Gdp/gtp Exchangementioning
confidence: 99%